2021
DOI: 10.1007/s10640-021-00625-2
|View full text |Cite
|
Sign up to set email alerts
|

International Environmental Agreement and Trade in Environmental Goods: The Case of Kyoto Protocol

Abstract: The Kyoto Protocol has received much criticism for its effectiveness as well as the spillover effect (i.e. carbon leakage and competitiveness loss). This paper provides the first evidence for the effect of the Kyoto Protocol on the bilateral trade in environmental goods, which can mitigate and prevent environmental damage. Using the generalized synthetic control method, I construct the counterfactual of trading pairs with Kyoto commitment and show that the export of environment goods by Kyoto countries increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The few existing papers exploring the trade effects of IEAs generate inconclusive results. Studies of the Kyoto Protocol find that membership to this agreement reduces trade in general (Aichele & Felbermayr, 2013;Kim, 2016) but increases trade in environmental goods (Tran, 2022). An article on the Basel Convention finds no evidence that the Convention has reduced the amount of waste being shipped among parties (Kellenberg & Levinson, 2014) while an article on the Rotterdam Convention and the Stockholm Convention finds that their ratification reduces trade of hazardous substances from OECD to non-OECD countries (Núñez-Rocha & Martínez-Zarzoso, 2019).…”
Section: The Literature On the Trade Effects Of Ieasmentioning
confidence: 99%
“…The few existing papers exploring the trade effects of IEAs generate inconclusive results. Studies of the Kyoto Protocol find that membership to this agreement reduces trade in general (Aichele & Felbermayr, 2013;Kim, 2016) but increases trade in environmental goods (Tran, 2022). An article on the Basel Convention finds no evidence that the Convention has reduced the amount of waste being shipped among parties (Kellenberg & Levinson, 2014) while an article on the Rotterdam Convention and the Stockholm Convention finds that their ratification reduces trade of hazardous substances from OECD to non-OECD countries (Núñez-Rocha & Martínez-Zarzoso, 2019).…”
Section: The Literature On the Trade Effects Of Ieasmentioning
confidence: 99%
“…Maamoun (2019) uses the generalized synthetic control method (GSCM) to compare the emissions of industrialized countries participating in the Kyoto Protocol with their expected emissions had they not participated, and shows that the actual emissions are reduced by about 7% compared to the expected emissions under the "No-Kyoto" scenario. Specifically, the Kyoto Protocol encourages non-signatories to reduce carbon dioxide emissions while limiting carbon emissions of signatories by establishing cooperation mechanisms such as the joint implementation mechanism, the international emissions trading mechanism, and the clean development mechanism (Kuriyama and Abe, 2018;Tran, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, the Kyoto Protocol has also received criticism. In particular, the exclusion of developing countries from emissions targets has been portrayed as a fatal design flaw, and the countries' legal obligations differ under the principle of "common but differentiated responsibilities" (Maamoun, 2019;Tran, 2022). Nevertheless, the Kyoto Protocol restricts the carbon dioxide emissions through its unique cooperation mechanisms and emission reduction methods (Madaleno and Moutinho, 2017;Mohammed, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Aichele and Felbermayr (2015) found that countries making binding commitments under the Kyoto Protocol increased their embodied carbon imports from noncommitted countries. Tran (2021) examined the impact of the Kyoto Protocol on the trade of environmental goods and found that the exports of environmental goods by Kyoto countries increased significantly after the Protocol entered into force. Ederington et al (2019) found that the ratification of an international environmental agreement has negative short-term impacts on exports of the manufacturing industry with medium emission intensity but positive long-term impacts due to shifts to cleaner products.…”
Section: Introductionmentioning
confidence: 99%